PERAN BRAND IMAGE MEMEDIASI PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI KOTA DENPASAR - Armayani, Astari; Jatra, I Made (E-Jurnal Manajemen; Vol 8 No 8 (2019)DO - 10.24843/EJMUNUD.2019.v08.i08.p20, 2019)
The purpose of this study is to provide an explanation of the influence of brand image on purchasing decisions, promotion of purchasing decisions, prices on purchasing decisions . The method used to determine the sample is non-probability in the form of purposive sampling with a sample size of 112 respondents. Data collection is done by distributing questionnaires directly and through online to Samsung smartphone product customers in Denpasar City. The analysis technique used is path analysis (path analysis) and sobel test. The test results from promotions and prices positively and significantly influence the brand image and decision to purchase Samsung smartphone products in the city of Denpasar. Brand image is able to mediate the influence of promotions and prices positively and significantly on purchasing decisions. This shows that the brand image has an important role in the promotion and consumer prices, thus increasing the decision to buy Samsung smartphone products in the city of Denpasar. The management of Samsung companies should be more aggressively conducting marketing mix so that consumers increasingly trust the performance of the Samsung company. Keywords : brand image, promotion, price and purchasing decision